THE ROLE OF TECHNOLOGY-BASED COUNSELING IN SUPPORTING PARENTS OF CHILDREN WITH SPECIAL NEEDS: A CASE STUDY IN AN URBAN AREA - Nararya Rahadyan Budiyono; Sunenti Sunenti (Sekolah Tinggi Agama Islam Kuningan, 2024)
Technology​ the more develop in various fields , including service counseling that is now accessible online . For parents child in need special , counseling based on technology become effective solution in the midst limitations time and access in the area urban areas . However, studies on the effectiveness of these services are still limited, especially in developing countries such as Indonesia. This study aims to analyze the role of technology-based counseling in supporting parents of children with special needs in urban areas, with a focus on effectiveness, accessibility, and challenges faced. This study used a descriptive qualitative method with a semi-structured interview technique on 20 parents in urban areas who use technology-based counseling services. Data were also collected through participant observation during counseling sessions. Data analysis was carried out using thematic analysis. The results of the study showed that technology-based counseling greatly helped parents in managing daily challenges, improving the quality of family life, and providing easier and more flexible access than face-to-face counseling. However, obstacles such as unstable internet connections and emotional limitations in virtual interactions are still challenges. This study also found that technology-based counseling can be an effective solution for families in urban areas if supported by better infrastructure and additional training for counselors.